Pengaruh Akuntabilitas Keuangan Daerah, Value For Money, Kejujuran, Transparansi dan Pengawasan Pemerintah Terhadap Pengelolaan Keuangan Daerah (Studi Pada Kantor Badan Keuangan dan Aset Daerah (BKAD) Kabupaten Malang dan Kota Malang) - Fadillah, Mulkan Ahmad; Sudaryanti, Dwiyani; Amin, Moh. (e_Jurnal Ilmiah Riset Akuntansi, 2024)
This study aims to examine the influence of regional financial accountability, value for money, honesty, transparency, and government supervision on regional financial management at the Regional Financial and Asset Agency (BKAD) in Malang Regency and Malang City. This research employed a purposive sampling method involving 71 respondents from BKAD officials. Data was analyzed using SPSS 25. The results showed that simultaneously, these variables significantly influenced regional financial management. Further analysis revealed that regional financial accountability and value for money had a positive and significant impact on regional financial management. Conversely, honesty and transparency showed a negative and significant impact. The variable of government supervision was not found to have a significant effect. These findings indicate that increased accountability and efficiency in budget utilization can improve the quality of regional financial managementKeywords: Regional financial management, financial accountability, value for money, honesty, transparency, government supervision